KEWAJIBAN NOTIFIKASI AKUISISI OLEH PERUSAHAAN (STUDI PERBANDINGAN: INDONESIA DENGAN REPUBLIK RAKYAT TIONGKOK): Requirement of Acquisition Notification by Companies (Comparative Study: Indonesia And The People's Republic Of China) - Valois, Yoana Thersia Listoravina; Nurbaiti, Siti (Faculty of Law, Universitas Trisakti, 2025)
In the midst of the progress of the business world today, competition between companies is getting tougher in order to keep up with the times. One way to grow is by making acquisitions. In the acquisition process, companies must provide notification to the Business Competition Authority. This research examines the issue of how the obligation of company acquisition notification between Indonesia and the People's Republic of China? The method used in this research is normative legal research, descriptive in nature, using secondary data, data collection is done by means of literature study, analysed qualitatively and deductive conclusions are drawn. The results illustrate that there are similarities and differences regarding notification obligations in Indonesia, which use the Post-Notification system based on Article 29 of Law 5/1999 and Pre-Notification based on Article 10 of Government Regulation 57/2010.Business actors will be subject to a sanction of IDR 1 billion per day of delay. Meanwhile, the People's Republic of China uses the Pre-Notification system based on Article 26 of the AML. Business actors may also be subject to a fine of RMB 500,000 if they do not carry out notification obligations.